R-Factor Transfer in Selenite and Tetrathionate Broths - Gardner, Pierce (1971)
After overnight incubation of R(+)Escherichia coli with R(−)Salmonella typhimurium in selenite and tetrathionate with Brilliant Green (TBG) broths, R-factor transfer was demonstrated in 10 of 12 experiments. R-factor transfer in these enrichment broths occurred at a markedly reduced frequency in comparison to that in Trypticase soy broth, apparently due to an adverse effect either on the viability of the donor E. coli or the conjugation process itself. Transfer of R factors in commonly used enrichment broths may give rise to falsely resistant antibiotic patterns in Salmonella. However, the frequency of R-factor transfer is so low that it is unlikely to affect significantly the interpretation of R-factor studies.